2023
DOI: 10.1007/s00134-022-06953-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between acute disease severity and one-year quality of life among post-hospitalisation COVID-19 patients: Coalition VII prospective cohort study

Abstract: Purpose To assess the association between acute disease severity and 1-year quality of life in patients discharged after hospitalisation due to coronavirus disease 2019 (COVID-19). Methods We conducted a prospective cohort study nested in 5 randomised clinical trials between March 2020 and March 2022 at 84 sites in Brazil. Adult post-hospitalisation COVID-19 patients were followed for 1 year. The primary outcome was the utility score of EuroQol five-dimension three-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 38 publications
4
24
1
8
Order By: Relevance
“…In line with this, severity of disease has in previous literature been reported to be associated with more remaining health related symptoms at follow-up 9. As previously reported about the first wave survivors in the cohort, their quality of life was reduced compared with the general Swedish population,8 also consistent with data from other populations 31…”
Section: Discussionsupporting
confidence: 89%
“…In line with this, severity of disease has in previous literature been reported to be associated with more remaining health related symptoms at follow-up 9. As previously reported about the first wave survivors in the cohort, their quality of life was reduced compared with the general Swedish population,8 also consistent with data from other populations 31…”
Section: Discussionsupporting
confidence: 89%
“…Patients requiring mechanical ventilation may also be at a greater risk for lower health-related quality of life and worse mortality. 61 Blanco et al 62 examined the respiratory function of severe cases of PASC and reported that diffusion deficit (DLCO [diffusing capacity for carbon monoxide] <80%) was present 100 days after hospital discharge. Other than lung function defects, multiple sequelae, including cardiac injury, correlate with initial disease severity and improve over time in most patients.…”
Section: Post Covid-19 Pneumoniamentioning
confidence: 99%
“…Over the first 3 years of the pandemic, hospital admissions and mortality among people infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) have decreased owing to the availability of effective vaccines and therapies 2 . With the growing number of patients recovering from COVID‐19, attention has focused on multi‐system symptoms and quality of life in convalescent individuals 3–5 . To date, emerging epidemiological and clinical evidence has revealed persistent health issues following COVID‐19, which are referred to as long COVID or post‐COVID‐19 condition 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…2 With the growing number of patients recovering from COVID-19, attention has focused on multi-system symptoms and quality of life in convalescent individuals. [3][4][5] To date, emerging epidemiological and clinical evidence has revealed persistent health issues following COVID-19, which are referred to as long COVID or post-COVID-19 condition. 6,7 However, the current understanding of long COVID remains limited, and there is no general consensus on its long-term consequences.…”
mentioning
confidence: 99%